Special taxpayers and incentive schemes - Woellner, R.; Barkoczy, S.; Murphy, S.; Evans, Christopher; Pinto, Dale (CCH, 2014)
The tax law contains special rules for taxing certain kinds of taxpayers due to their particular characteristics or status. It also contains several tax expenditure programs designed to encourage particular kinds of activities. This chapter examines the way in which the tax law deals with certain special taxpayers and incentive schemes.